Queerowanie gier AAA na przykładzie serii Assassin’s Creed – możliwości i zagrożenia - Repeć, Ewelina (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article is, fundamentally, cross-sectional. As its subject, the author chose the most recent installments of the Assassin’s Creed franchise – two digital games, Odyssey (2018) and Valhalla (2020) by Ubisoft. This analysis focuses mainly on the representation of minorities, especially the queer one. It also studies female characters and Ubisoft’s marketing strategies. The main goal of the article is to point out certain possibilities which arise due to the ongoing process of increased inclusivity, as well as potential dangers stemming from underrepresentation. Digital games have unique potential and can provide opportunities to explore one’s own identity. On the other hand, inappropriate creative strategies may result in a danger of perpetuating and strengthening harmful stereotypes. Therefore, it is equally important for developers and consumers alike to eliminate potentially detrimental elements in video games and attempt to build an inclusive and prejudice-free medium.